ANALISIS KLAIM PASIEN COVID-19 PADA PRODUK MiSMART HEALTH CARE SYARIAH MANULIFE INDONESIA - Annisya Nuriva Handayani; Mira Rahmi (Veteran Economics, Management, & Accounting Review, 2022)
MiSmart Health Care Syariah product claims have 4 stages, namely notification, proof of documents, investigation, and payment of claims. The implementation of Covid-19 patient claims on MiSmart Health Care Syariah products is also in accordance with Fatwa No.21/DSN-MUI/X/2001, namely Claims are paid according to the amount agreed at the beginning of the contract, Manulife Indonesia pays claims according to the premium amount, Manulife Indonesia is located as a fund manager (mudharib) for premiums paid by insurance participants while the customer is the owner of the money (shohibul mal) and fulfills its obligations by approving every claim submitted by the customer in accordance with the provisions of the policy, while according to POJK No.69/POJK.05 /2016, namely Manulife Indonesia makes payment of claims for Covid-19 patients in no more than 14 days, in collaboration with Admedika as an assessor and investigation of claims administration, submission of proof of claim documents in accordance with existing regulations and payment of claims will be made by the finance department of Manulife Indonesia.  Keywords: Claims; Covid-19; Sharia Insurance AbstrakKlaim produk MiSmart Health Care Syariah terdapat 4 tahap, yaitu pemberitahuan, bukti dokumen, penyelidikan, dan pembayaran klaim. Pelaksanaan klaim pasien Covid-19 pada produk MiSmart Health Care Syariah juga telah sesuai dengan Fatwa No.21/DSN-MUI/X/2001, yaitu klaim dibayarkan sesuai dengan jumlah yang disepakati dalam awal akad, Manulife Indonesia membayarkan klaim sesuai dengan besaran premi, Manulife Indonesia berkedudukan sebagai pengelola dana (mudharib) atas uang premi yang dibayarkan peserta asuransi sementara nasabah berkedudukan sebagai pemilik uang (shohibul mal) dan memenuhi kewajibannya dengan menyetujui setiap klaim yang diajukan nasabah sesuai dengan ketentuan polis, sedangkan menurut POJK No.69/POJK.05/2016 yaitu Manulife Indonesia melakukan pembayaran klaim pasien Covid-19 tidak lebih dari 14 hari, bekerjasama dengan Admedika sebagai penilai dan penyelidikan administrasi klaim, penyerahan bukti dokumen klaim sesuai ketentuan yang ada dan Pembayaran klaim akan dilakukan oleh bagian keuangan dari pihak Manulife Indonesia.Kata Kunci: Asuransi Syariah; Covid-19; Klaim.